Speckle tracking echocardiography could detect the difference of pressure overload-induced myocardial remodelling between young and adult rats. Issue 163 (26th February 2020) - Niu, Pei; Li, Li; Yin, Zhongjie; Du, Jie; Tan, Wenchang; Huo, Yunlong
Abstract : The assessment by speckle tracking echocardiography (STE) provides useful information on regional and global left ventricular (LV) functions. The aim of the study is to investigate if STE-based strain analysis could detect the difference of pressure overload-induced myocardial remodelling between young and adult rats. Physiological, haemodynamic, histological measurements were performed post-operatively in young and adult rats with transverse aortic constriction (TAC) as well as the age-matched shams. Two-way ANOVA was used to detect the statistical difference of various measured parameters. Pressure overload decreased the ejection fraction, fractional shortening, d p /d t max and | d p / d t min |, but increased the LV end-diastolic (ED) pressure in adult rat hearts for nine weeks after TAC operation than those in young rat hearts. Pressure overload also resulted in different changes of peak strain and strain rate in the free wall, but similar changes in the interventricular septum of young and adult rat hearts. The changes in myocardial remodelling were confirmed by the histological analysis including the increased apoptosis rate of myocytes and collagen area ratio in the free wall of adult rat hearts of LV hypertrophy when compared with the young. Pressure overload alters myocardial components in different degrees between young and adult animals. STE-based strain analysis could detect the subtle difference of pressure overload-induced myocardial remodelling between young and adult rats.